The diagnostic challenge of pneumocystis pneumonia and COVID‐19 co‐infection in HIV. Issue 4 (22nd February 2021) - Broadhurst, Alistair G.B.; Lalla, Usha; Taljaard, Jantjie J.; Louw, Elizabeth H.; Koegelenberg, Coenraad F.N.; Allwood, Brian W.
Abstract: Coronavirus disease 2019 (COVID‐19) and pneumocystis pneumonia (PCP) share many overlapping features and may be clinically indistinguishable on initial presentation in people living with HIV. We present the case of co‐infection with COVID‐19 and PCP in a patient with progressive respiratory failure admitted to our intensive care unit where the dominant disease was uncertain. This case highlights the difficulty in differentiating between the two diseases, especially in a high HIV prevalence setting where PCP is frequently diagnosed using case definitions and clinical experience due to limited access to bronchoscopy, appropriate laboratory testing, and computed tomography scans. In addition, diagnostic testing may yield false‐negative results in both diseases, and clinician awareness to the overlap and pitfalls is essential if COVID‐19 becomes endemic in such settings. Abstract : We present the case of a 54‐year‐old male with newly diagnosed advanced HIV who presented with clinical, biochemical, and radiological features that were consistent with both pneumocystis pneumonia (PCP) and coronavirus disease 2019 (COVID‐19). He subsequently tested positive for both diseases; however, the contribution of each disease to his progressive respiratory failure is unclear.